Bridging Diffable-Non-Diffable Interactions Through Theatre: A Case Study of Teater Cangkir, Kabupaten Tegal - Manurung, Gregorius Tri Hendrawan; Umam, Khothibul (Proceedings International Conference of Culture and Sustainable Development; Vol 1 (2023): PROCEEDINGS ICOCAS, 2023)
This research was conducted to examine the practices of Teater Cangkir which bridges the interactions of the diffable and non diffable group in Tegal, Indonesia. The method used in this research is Sociology of Art approach which focuses on the production process and the public’s reception of Teater Cangkir’s performances. Data was collected through observations and in-depth interview. Observation was used to collect data of Teater Cangkir’s production process. While the interview was used to align the data that has been previously obtained.